2013
DOI: 10.4081/gh.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of landscape factors and management decisions on spatial and temporal patterns of the transmission of chronic wasting disease in white-tailed deer

Abstract: Abstract. Chronic wasting disease (CWD) has been reported in white-tailed deer at the border of the US states of Illinois and Wisconsin since 2002. Transmission of infectious prions between animals and from the environment has resulted in spatial and temporal structure observable in the spatio-temporal patterns of reported cases. Case locations of 382 positive cases from 28,954 deer tested between 2002 and 2009 provided insight into the potential risk factors and landscape features associated with transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
(54 reference statements)
5
31
1
Order By: Relevance
“…For example, 140 positive cases were detected over a 7‐year span in the central Appalachian region from samples collected by all methods of surveillance (i.e., hunter harvest, road‐kills, and sharpshooting; Evans et al ). Over a comparable time period using the same methods of surveillance, more than twice and nearly 3 times the number of positives were detected in Wisconsin's disease eradication zone ( n = 316; Grear et al ) and along the Wisconsin‐Illinois border ( n = 382; O' Hara Ruiz et al ), respectively. The lower number of positives in this region of the Northeast (Evans et al ) compared to the agricultural‐forest dominated landscape of the Midwest with comparable sampling efforts would suggest a lower potential for spread of CWD because of greater isolation of deer matriarchal groups in large homogenous forests or the epidemic is in an earlier stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 140 positive cases were detected over a 7‐year span in the central Appalachian region from samples collected by all methods of surveillance (i.e., hunter harvest, road‐kills, and sharpshooting; Evans et al ). Over a comparable time period using the same methods of surveillance, more than twice and nearly 3 times the number of positives were detected in Wisconsin's disease eradication zone ( n = 316; Grear et al ) and along the Wisconsin‐Illinois border ( n = 382; O' Hara Ruiz et al ), respectively. The lower number of positives in this region of the Northeast (Evans et al ) compared to the agricultural‐forest dominated landscape of the Midwest with comparable sampling efforts would suggest a lower potential for spread of CWD because of greater isolation of deer matriarchal groups in large homogenous forests or the epidemic is in an earlier stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of disease spread are complex; understanding them involves many areas of research (e.g., biochemistry [47] or landscape variables [48]). We examined the genetic aspects of the spread of CWD, with the goal of contributing insights useful for containing and if possible eliminating (or at least reducing) chronic wasting disease among wild deer populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in Illinois suggested that there was a spatial correlation of CWD risk with alkaline soils, such as those found in the northern part of the state where CWD clusters concentrate. 35 In addition, there was evidence of an association between CWD risk and a lower percentage of clay and a higher percentage of sand in soils. The analysis by Ruiz et al 35 was carried out at a spatial scale based on geographic units of one square mile, thus making direct comparison difficult with the current study carried out at the level of the county.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, there was evidence of an association between CWD risk and a lower percentage of clay and a higher percentage of sand in soils. The analysis by Ruiz et al 35 was carried out at a spatial scale based on geographic units of one square mile, thus making direct comparison difficult with the current study carried out at the level of the county. The collection of field samples and more precise measures of soil ingestion by deer in this region would help to better elucidate the relationship between metals, soils and CWD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation